Role of MDCT renal angiography in determining the anatomical eligibility for renal sympathetic denervation in resistant hypertensive patients - Dena Abd El Aziz El Sammak; Mohammad Abd Alkhalik Basha; Mohammad El Tahlawi (The Egyptian Journal of Radiology and Nuclear Medicine, 2018)
Objective: Aim of this study was to assess role of Multidetector computed tomography (MDCT) Renal Angiography in determining the anatomical eligibility for renal sympathetic denervation in resistant hypertensive patients. Subjects and methods: This study included 30 patients, referred from hypertension unit in Zagazig University Hospital, with refractory systemic hypertension [an office blood pressure (BP) >140/90 mmHg despite treatment with at least three drugs, including a diuretic in adequate doses]. All cases were performed using a 128-slice MDCT scanner. All data were transferred to an imaging workstation for reconstruction and analysis. Axial source images were post-processed to produce multiplanar reformation, curved planar reformation, maximum intensity projection and volume rendering images. Results: Most patients (46.7%) had an A1/A1 type renal artery (RA). 66.7% were completely eligible (CE), 23.3% were partially eligible (PE), and 10% were non eligible (NE). Regarding intraobserver agreement; concordance between two readings by the same radiologist was in 96.7%, while discordance was in 3.3%. Regarding interobserver agreement; concordance between two radiologists was in 93.3% while discordance was in 6.7%. Conclusion: MDCT renal angiography gives valuable knowledge to the interventional radiologist and cardiologist before renal artery denervation (RDN) to increase the success rate. Keywords: MDCT renal angiography, Eligibility, Resistant hypertension, Renal sympathetic denervation